1952
DOI: 10.1071/ch9520541
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Errors in the Amperometric and Starch Indicator Methods for the Titration of Millinormal Solutions of Iodine andThiosulphate

Abstract: The amperometric method of Foulk and Bawden when applied to the titration of 0.001N thiosulphate solutions with iodine is shown to be more precise and to have a smaller " blank" than that using starch as indicator. With simple precautions the method has an accuracy of at least 0.1 per cent. over the range pH 1-8, but at higher pH there is serious error due to sulphate formation. The magnitudes of other errors are determined and it is shown that all can be rendered negligible in titrations of milli-normal solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

1954
1954
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
2
5
0
1
Order By: Relevance
“…Similar comparisons were repeated five times using surface waters of the Philippine Sea, and the endpoint bias occurred consistently; more feeding of titrant was necessary in the potentiometric titration than in the starch method by 0.7 to 0.9% of titrant volume of the latter method. This difference in the endpoints is in agreement with the fact that the amperometric endpoint detection requires more feeding of titrant than the starch method (Bradbury and Hambly, 1952;Knowles and Lowden, 1953;Culberson and Huang, 1987;Culberson et al, 1991). Bradbury and Hambly (1952) concluded that the visual endpoint with starch is significantly different from the equivalence points detected by amperometry.…”
Section: Comparison Of Visual Starch and Potentiometric Endpoint Indisupporting
confidence: 69%
See 1 more Smart Citation
“…Similar comparisons were repeated five times using surface waters of the Philippine Sea, and the endpoint bias occurred consistently; more feeding of titrant was necessary in the potentiometric titration than in the starch method by 0.7 to 0.9% of titrant volume of the latter method. This difference in the endpoints is in agreement with the fact that the amperometric endpoint detection requires more feeding of titrant than the starch method (Bradbury and Hambly, 1952;Knowles and Lowden, 1953;Culberson and Huang, 1987;Culberson et al, 1991). Bradbury and Hambly (1952) concluded that the visual endpoint with starch is significantly different from the equivalence points detected by amperometry.…”
Section: Comparison Of Visual Starch and Potentiometric Endpoint Indisupporting
confidence: 69%
“…This difference in the endpoints is in agreement with the fact that the amperometric endpoint detection requires more feeding of titrant than the starch method (Bradbury and Hambly, 1952;Knowles and Lowden, 1953;Culberson and Huang, 1987;Culberson et al, 1991). Bradbury and Hambly (1952) concluded that the visual endpoint with starch is significantly different from the equivalence points detected by amperometry. However, the difference in the endpoint among the detection methods does not necessarily yield difference in oxygen concentration as long as the titrant is calibrated by the same detection method as used for samples.…”
Section: Comparison Of Visual Starch and Potentiometric Endpoint Indisupporting
confidence: 69%
“…The starch endpoint occurs slightly before the amperometric endpoint (Bradbury and Hambly, 1952;Knowles and Lowden, 1953). There is some evidence (Culberson and Huang, 1987) that the difference between the two endpoints varies with salinity.…”
Section: Low Oxygen Intercalibrationmentioning
confidence: 99%
“…The oxygen concentration corresponding to a given blank is calculated for a nominal volume of 125 ml , 1952;Knowles and Lowden, 1953;Culberson and Huang, 1987).…”
mentioning
confidence: 99%
“…Besonders einl~ssliche l~bersichten fiber die m6glichen Fehlerquellen der titrirnetrischen Methode geben GRASSHOFF [13], CARPENTER [8] und BRADBURY [5]. MONTGOMERY [30] widmet sich irn besondern auch den Fehlern bei der Probenahme.…”
Section: ~Berblickunclassified